PEMANFAATAN APLIKASI EXCEL UNTUK PENGOLAHAN NILAI SUMATIF SISWA TERHADAP PEMBELAJARAN PAI - Amalia Dwi Fitriani; Robiyatul Adawiyah; Bakti Fatwa Anbiya (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2024)
Education plays a central role in the advancement of a nation, while technological progress becomes crucial in the context of education and the increasingly significant evaluation of educational quality. This article aims to explore and implement technology, particularly Excel software, in optimizing grade processing. Using qualitative descriptive research methods, this study provides an explanation of the use of Excel as an assessment tool in learning. By utilizing Excel features such as formulas, filters, and formatting, this research demonstrates that this technology can be a powerful tool in creating a structured, easy-to-understand, and adaptable system tailored to individual needs. The results of this study highlight the potential of Excel as an effective tool in simplifying the summative grading process in Islamic Education (PAI), offering educators the opportunity to design more measurable and adaptive assessments according to student needs. Therefore, the implications of this research suggest that the use of Excel technology in the context of Islamic Education can significantly contribute to enhancing the quality of learning and educational evaluation overall.